2004
DOI: 10.1074/jbc.m311658200
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the Endonuclease Activity of the Baculovirus Alkaline Nuclease for Single-stranded DNA

Abstract: Baculoviruses contain double-stranded (ds), 1 circular, supercoiled DNA genomes of 100 -180 kbp and belong to the family Baculoviridae, which includes two genera, the granuloviruses and the nucleopolyhedroviruses (NPVs) (1, 2). One NPV, Autographa californica multiple nucleocapsid NPV (AcMNPV), is widely used as a model for analysis of baculovirus replication in infected cells and for the generation of recombinant viruses for the expression of foreign genes. Replication of baculovirus genomes proceeds in discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 57 publications
0
32
1
2
Order By: Relevance
“…lef3 was originally identified as one of six genes required for viral DNA replication in transient assays (22). LEF3 has been shown to be an SSB protein and may regulate the viral protein alkaline nuclease (15,34). Recently, a lef3 knockout virus was constructed that deleted the lef3 ORF and the 5= end of ac68 (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lef3 was originally identified as one of six genes required for viral DNA replication in transient assays (22). LEF3 has been shown to be an SSB protein and may regulate the viral protein alkaline nuclease (15,34). Recently, a lef3 knockout virus was constructed that deleted the lef3 ORF and the 5= end of ac68 (53).…”
Section: Discussionmentioning
confidence: 99%
“…lef3 was identified as one of the genes essential for baculovirus DNA replication by transient analyses and recently by construction of a KO mutant (22,53). LEF3 has also been shown to interact with the viral proteins P143 and alkaline exonuclease, which are involved in viral DNA replication and recombination (26,33,34). Using plasmid transfection experiments, it has also been shown that P143, a DNA helicase with ATPase and DNA binding activities, is dependent upon LEF3 for transport to the nucleus (15,32,50).…”
mentioning
confidence: 99%
“…LEF-3 is also responsible for transporting P143, a predicted DNA unwinding (helicase) protein, into the nucleus, where it is required for viral DNA replication (26,29,45). LEF-3 may also regulate the activity of a viral alkaline nuclease (AN) during viral DNA replication (32). We have previously mapped the region carrying the nuclear localization signal of LEF-3 to residues 26 to 32 within the N-terminal 56-amino-acid domain (1,7).…”
mentioning
confidence: 99%
“…We have also found that it has an endonuclease activity and that this activity appears to be specific for singlestranded regions of DNA most likely caused by physical distortions that occur as a result of the negative superhelicity of the DNA (19). Furthermore, this endonucleolytic activity was associated with a high degree of specificity for secondary cleavage on the strand opposite the initial nick such that, rather than random endonucleolytic cleavage, the result is specific cleavage of both DNA strands at or very near the same position.…”
Section: Discussionmentioning
confidence: 99%